The Origins of the Generic Mapping Tools: From Table Tennis to Geoscience - Paul Wessel (Perspectives of Earth and Space Scientists)
Abstract The Generic Mapping Tools (GMT) is one of the most used toolsets in the Earth, Ocean, and Planetary sciences, originating as far back as the 1980s. It is an early example of an open‐source software code modeled after contemporaneous UNIX tools, and it was one of the first to employ PostScript as its graphics language and netCDF for binary files to ensure portability across different computing platforms. Here I trace the origin and evolution of GMT to the present day. The additions of MATLAB, Python, and Julia wrappers around the GMT C Application Program Interface (API) are now introducing GMT to numerous new and younger users and the platform shows no sign of diminishing after almost 40 years; in fact, usage continues to expand. Pursuing GMT for fun (and funding) has positively affected other areas of my scientific interests, and my new research modules continue to be added to GMT. The future holds many promises but will require formation and leadership of communities to steer and maintain the essential science tools that have served us well for many decades.